Study on the Influence of Borehole Water Content on Bolt Anchoring Force in Soft Surrounding Rock - Pandong Zhang; Lin Gao; Pengze Liu; Yongyin Wang; Ping Liu; Xiangtao Kang (Shock and Vibration)
In order to further reveal the influence mechanism of borehole water content on anchoring force in soft surrounding rock, three different research methods are used. Firstly, through theoretical analysis, it reveals that borehole water content will affect the cohesion of anchoring agent and then leads to the decrease of anchoring force. Secondly, through experimental analysis and numerical simulation of the influence of different boreholes water content on the anchoring force, it indicates that the borehole water content has a weakening effect on the mechanics characteristics of bolts significantly. When the borehole water content is less than 15 mL, the influence of borehole water content on anchoring force is weak for a given borehole length. When the borehole water content is greater than 15 mL, the anchoring force decreases greatly with the increase of borehole water content for a given borehole length and the decline of anchorage force is more than 30%. At the same time, through the experimental analysis, it reveals that the failure type of bolt in weak surrounding rock is the typical failure of anchorage force where the fracture goes far into the surrounding rock. Thus, in practical operation, reasonably controlling the borehole water content (rate) within the critical value can improve the bolt support effect and reduce the support cost.